Increased migration of human mesenchymal stromal cells by autocrine motility factor (AMF) resulted in enhanced recruitment towards hepatocellular carcinoma. - Juan Bayo; Esteban Fiore; Jorge B Aquino; Mariana Malvicini; Manglio Rizzo; Estanislao Peixoto; Oscar Andriani; Laura Alaniz; Flavia Piccioni; Marcela Bolontrade; Osvaldo Podhajcer; Mariana G Garcia; et al. (PLoS ONE, 2014)
BACKGROUND AND AIMS: Several reports described the migration of human mesenchymal stromal cells (MSCs) towards tumor-released factors. Autocrine motility factor (AMF) is produced by several tumors including hepatocellular carcinoma (HCC). The aim of this study was to analyze AMF involvement on MSC migration towards human HCC. METHODS: Production of AMF by HCC tumors was evaluated by western analysis. The effects of AMF on MSCs from different sources (bone marrow, adipose tissue and perivascular cells from umbilical cord) were analyzed using in vitro migration assay; metalloproteinase 2 (MMP2) activity and expression of critical genes were studied by zymography and qRT-PCR, respectively. To assess AMF involvement on the in vivo MSC migration, noninvasive fluorescence imaging was performed. To test the effect of AMF-primed MSCs on tumor development, in vitro proliferation and spheroids growth and in vivo tumor volume were evaluated. RESULTS: AMF produced by HCC was found to induce migration of different MSCs in vitro and to enhance their MMP2 activity. Stimulation of MSCs with recombinant AMF (rAMF) also induced the in vitro adhesion to endothelial cells in coincidence with changes in the expression levels of MMP3, AMF receptor, caveolin-1, and -2 and GDI-2. Importantly, stimulation of MSCs with rAMF increased the in vivo migration of MSCs towards experimental HCC tumors. AMF-priming of MSCs did not induce a pro-tumorigenic effect on HCC cells neither in vivo nor in vitro. CONCLUSION: AMF plays a role in MSC recruitment towards HCC. However, its ability to increase MSC migration to HCC for therapeutic purposes merits further evaluation.